Biocomputing : informatics and genome projects - Smith, Douglas W. (Douglas Wemp), 1938- (Academic Press, 1994)
The results of today's genome projects promise enormous medical and agricultural benefits and point to a new predictive approach to the conduct of future research in biology. Biocomputing: Informatics and Genome Projects represents a survey of the needs and objectives of genome projects as of the early 1990's. It provides the groundwork necessary to understand genome-related informatics, including computational and database storage objectives. The book covers four general areas: automated laboratory notebooks, nucleic acid sequence analysis, protein structure, and database activities.